Public budgeting and management. - Steiss, Alan Walter (Lexington, Mass., Lexington Books, 1972)
The book describes strategic planning and urban management, budget analysis, and scheduling and control of public activities required for significant long-term professional training.
Bibliography: p. 333-345.
sju 24/01/2019
Loans
Keywords: Program budgeting; Public administration; Decision making